Perception on COVID-19 in health workers versus other activities, Casanare-Colombia, 2020 - Castañeda-Porras, Oneida (2021)
Introduction. On 2020-03-11 World Health Organization classified COVID-19 as a pandemic. In Colombia, department of Casanare declared sanitary emergency on 2020-03-16 and the President of the Republic declared economical, social and ecological emergency on 2020-03-17; five days later the first case at department was confirmed. Objective. To survey knowledges, attitudes, and practices (KAP) on department's population. Methods. Descriptive cross-sectional on Knowledge-Attitudes-Practices (KAP) plus socio-demographic characterization on population (435.195 dwellers). Sampling by city and decennial age-group using Statcalc, Epi-Info® 7.2.2.2. Data gathering executed with Google Formularies tool through WhatsApp, Facebook social networks. Descriptive analysis with Epi Info™7.2.2.2 y Stata® 13. Results. Survey rendered 1.120 responses, resulting as follows: Socio-demographic: 541 (48,9%) living at Yopal, 779 (69,6%) women; age 36 ± 12 yr-old; 919 (82,1%) were 20-49 yr-old, 582 (50,2%) married/consensual union. By activity: 251 (22,4%) health workers, 869 (77,6%) others. Education: 565 (50,4%) professionals, 157 of the latter postgraduates (27,8%); recognized ethnic group 113 (10,1%). Knowledges: description as viral/infectious disease 695 (62,1%); contagion through sneezing 1077 (96,2%); it's a cold 155 (13,8%); mild cough 965 (86,2%); attention route unknown 334 (29,8%). Attitudes: 657 (58,6%) left home for food, work or chores; prevention is for everyone, 985 (85,5%). Practices: 825 (95,0%) informated by TV/radio; main measure not leaving home 1.109 (99,0%); no health consultation in the last 30 days 890 (79,5%); to call attention line if symptoms 896 (80,0%). Prevention by isolation/quarantine 809 (72,2%); authority must do inspection/vigilance/control 796 (71,1%). Discussion. On COVID-19, population exhibited basic knowledge, good attitude and cooperative, even demanding position with local, regional Executive. It is recommended to maintain/strengthen Inspection / Vigilance / Control actions and Information / Education / Communication to citizens.